Management of the anticoagulated trauma patient in the emergency department: a survey of current practice in England and Wales. Issue 6 (4th January 2016) - Battle, Ceri E; Lecky, Fiona E; Stacey, Tom; Edwards, Antoinette; Evans, Phillip A
Abstract : Objective: The aim of this study was to investigate current management of the anticoagulated trauma patient in the emergency departments (EDs) in England and Wales. Methods: A survey exploring management strategies for anticoagulated trauma patients presenting to the ED was developed with two patient scenarios concerning assessment of coagulation status, reversal of international normalised ratio (INR), management of hypotension and management strategies for each patient. Numerical data are presented as percentages of total respondents to that particular question. Results: 106 respondents from 166 hospitals replied to the survey, with 24% of respondents working in a major trauma unit with a specialist neurosurgical unit. Variation was reported in the assessment and management strategies of the elderly anticoagulated poly-trauma patient described in scenario one. Variation was also evident in the responses between the neurosurgical and non-neurosurgical units for the head-injured, anticoagulated trauma patient in scenario two. Conclusion: The results of this study highlight the similarities and variation in the management strategies used in the EDs in England and Wales for the elderly, anticoagulated trauma patient. The variations in practice reported may be due to the differences evident in the available guidelines for these patients.